Medical encounters with young unaccompanied refugees: a qualitative study among general practitioners and physicians in migrant health clinics in Norway and Denmark - Gjertrud Moe; Bente Prytz Mjølstad; Linn Okkenhaug Getz; Morten Sodemann; Borgunn Ytterhus (Scandinavian Journal of Primary Health Care)
Objective This study examines the experiences of clinical encounters with young unaccompanied refugees in Norway and Denmark among both general practitioners (GPs) and physicians in migrant health clinics (MHC physicians), and it identifies important aspects that should be taken into consideration for improving the quality of healthcare for these patients.Methodology Ten individual in-depth interviews with physicians in Norway and Denmark were conducted and analysed using interpretative phenomenology. Axel Honneth’s theory of recognition was our theoretical lens.Results The physicians described these patients as vulnerable individuals. They adopted a variety of approaches in their encounters with young unaccompanied refugees spanning from a ‘holistic’ to an ‘instrumental’ approach. Those who described an instrumental approach focused on understanding and categorising symptoms from a biomedical perspective, while those describing a holistic approach considered ‘the whole person’ within their everyday context. Those with a more holistic approach also expressed the importance of interdisciplinary collaboration and defined work-divide. Relationships of trust between physicians and the young unaccompanied refugees were shown to be an important facilitator for adequate healthcare, but this required availability, continuity, and dialogue.Conclusion Our results highlight how physicians’ encounters with vulnerable young refugees actualize previously documented contrasts between holistic and instrumental approaches in clinical work. We argue that recognition in healthcare is conditional on physicians taking a holistic approach. This approach can help build relationships of trust and can support interdisciplinary collaboration. Moreover, such an approach can facilitate the essential components of Honneth’s theory of recognition, namely social esteem and emotional support. Barriers to greater interdisciplinary collaboration in healthcare services need to be addressed at the system level.